ESTIMATING NAIRU: THE MOROCCO CASE - Elalaoui, Aicha; Ezzahid, Elhadj; Eladnani, M. Jallal (European Scientific Journal, ESJ, 2014)
The concept of NAIRU summarized the observed negative correlation between the unemployment rate and the inflation rate for a number of countries. This correlation persuaded some analysts of the impossibility for governments to simultaneously target both low unemployment and price stability. Therefore, it was government’s role to seek a point on the trade-off between the two objectives which matched a domestic social consensus. In this paper, we intend to estimate the Moroccan’s NAIRU for 1998Q1-2012Q4 period by applying the Kalman filter.